2001
DOI: 10.1038/labinvest.3780271
|View full text |Cite
|
Sign up to set email alerts
|

A High Frequency of Allelic Loss in Oral Verrucous Lesions May Explain Malignant Risk

Abstract: SUMMARY:Verrucous carcinoma (VC), a variant of squamous cell carcinoma (SCC), is distinct from SCC in morphology and behavior. The underlying genetic changes involved in the development of VC and its precursor verrucous hyperplasia (VH) are unknown. This study determined whether chromosomal regions frequently lost during the development of SCC are also lost in the VH/VC variant. Twenty-five VH and 17 VC were analyzed for loss of heterozygosity (LOH) at 19 loci on 7 chromosome arms using microsatellite analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Approximately 47% of cases presented with LOH in a single marker, 10.5% in two markers, and 5.3% in all three markers located. Similarly, Poh et al evaluated verrucous carcinomas and verrucous hyperplasias for LOH at 9p21 and reported LOH events in 77% and 46%, respectively (19). As summarized in Table 2, the highest LOH rates in PVL patients occurred for the marker D9S171 (45.5%) followed by INFa (35.3%) and D9S1748 (26.3%).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Approximately 47% of cases presented with LOH in a single marker, 10.5% in two markers, and 5.3% in all three markers located. Similarly, Poh et al evaluated verrucous carcinomas and verrucous hyperplasias for LOH at 9p21 and reported LOH events in 77% and 46%, respectively (19). As summarized in Table 2, the highest LOH rates in PVL patients occurred for the marker D9S171 (45.5%) followed by INFa (35.3%) and D9S1748 (26.3%).…”
Section: Resultsmentioning
confidence: 96%
“…Chromosomal loss in the region 9p21 was assessed using three markers reported to be highly polymorphic in head and neck tumors, oral dysplasias, and oral verrucous lesions (16,17,19,(30)(31)(32)(33). Consideration to the markers relative location on chromosome 9p was also given.…”
Section: Resultsmentioning
confidence: 99%
“…Even in the presence of overall similar LOH patterns, OVC showed higher frequencies of loss at 4q and lower frequencies of loss at 17p. 24 The possible link among these structural and functional features with biological behavior and clinical outcome in OVCs is far from being understood and requires further investigations. In the present study, we have demonstrated that a routine amenable technique like hr DNA-FCM may be used for a more specific assessment of the OVC heterogeneity based on the analysis of the DI values of the DNA aneuploid sublines and their intralesional distribution.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Additionally, the higher expression of interleukin-1β and glutathione S-transferase pi isoenzymes and the allelic loss at 19 loci on seven different chromosome arms may also play an important role in the malignant transformation of VH. [12][13][14] Tumour protein p53, epidermal growth factor receptor and human epidermal growth factor receptor 3 expression can also be used to differentiate VH from VC and SCC. 15,16 Although Greer Jr et al found an association between the human papilloma virus and VH, the role of the virus in the malignant transformation of VH has yet to be confirmed.…”
Section: Discussionmentioning
confidence: 99%